THE MARKETING ETHICS OF ISLAMIC BANKS: A THEORETICAL STUDY - Havis Aravik; Hoirul Amri; Rahma Febrianti (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2022)
Ethics is a crucial component in human interaction, including in the field of marketing in Islamic banks. This article discusses the marketing ethics of Islamic banks: a theoretical study. The aim is to know the marketing ethics of Islamic banks comprehensively. The type of research used in this article is qualitative, which bases on library data focusing on text study and literature review. The results of this study show that there are several marketing ethics of Islamic banks such as promoting using gentle words, marketing is done with courtesy; being professional, fair, and transparent, placing customers as equal partners, do not consider competitors as enemies and working with a culture that following the Sunnah of the Prophet Muhammad.